Masalah Sampah Dan Pariwisata Papua Barat Daya - Senen, Karmila (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2023)
The relationship between waste and tourism has aspects of dependence on each other, the tourism sector will attract the attention of local and foreign tourists if the tourist area is clean and free from waste problems. Through this research, researchers are trying to find the source of the problem and efforts to overcome the problem of waste and tourism. This study uses qualitative methods including: observation, literature study, interviews with several informants, using other data analysis. researchers found facts on the ground that waste and tourism problems have become a problem that is often faced by tourism areas in the Southwest Papua region and the need for appropriate regulations to provide a deterrent effect and train discipline for the surrounding community and tourists to jointly maintain the cleanliness of the tourism area.